THE EFFECT OF ZEOLITE RATES ON GROWTH Cd SHOOT CONTENT AND YEILD OF THE LATTUCE (LACTUCA SATIVA L.) UNDER HEAVY METAL CADMIUM STRESS - Noertjahyani Noertjahyani; Nunung Sondari (Jurnal Zeolit Indonesia, 2009)
Cadmium is a non-essential heavy metal which can poison the plants. It is can inhibit the growth of plants moreover cause cell death. The lettuce is one of vegetables that are usually consumption on fresh. This plant adsorbing Cd from soil and accumulate on leaf greater than root. The study aimed to study the effect of zeolite rates to growth, cadmium shoot content, and lettuce (L. sativa) under Cd stress condition. The experiment was conducted on February until April 2009 at greenhouse of Agriculture Faculty, Winaya Mukti University Tanjungsari- Sumedang with elevation of 850 asl. The experiment design was using a Randomized Block Design (RBD) with 4 treatments and repeated six times. Zeolite rates treatments are 0 ton ha-1, 2 ton ha-1, 4 ton ha-1, and 6 ton ha -1 of zeolite. The result showed that given zeolite is not only could increase a plant height, leaf number, plant fresh weight, dry weight fade, root fade ratio, but also could reduce a Cd shoot content of lettuce. Application of 6 ton ha-1 zeolite not only gave the best effect to plant height age of 14 days after planting (dap), 21 dap, and 28 dap, leaf number/plant, fresh weight/plant, dry weight fade, root fade ratio, but also reduce a Cd shoot content of lettuce at 25,14%.